Deprotonation of safrole in the coordination entity of platinum (II). - Đà, Trần Thị; Chiến, Lê Xuân; Đĩnh, Nguyễn Hữu (Vietnam Journal of Chemistry, 2012)
The interaction  of K[Pt(Saf)Cl3] (Saf: safrole) with AgNO3, SnCl2, KOH  and ethanol-water solutions was investigated. For the first time, a dinuclear chelate ring complex [Pt2Cl2(Saf-1H)2], in which deprotonated safrole is bound up with platinum(II) both at benzene carbon and at ethylenic double bond of the side chain was isolated and characterized by elemental, thermal analysis, ESI MS, IR- and NMR spectroscopy.